PREDICTION OF WHITE FLOUR QUALITY OBTAINED BY INDUSTRIAL MILLING OF WHEAT - IULIANA APRODU; GEORGETA STOENESCU; VIOLETA IONESCU; IULIANA BANU (Scientific Study & Research: Chemistry & Chemical Engineering, Biotechnology, Food Industry)
In order to establish the relations between quality of the wheat and white flour obtained through industrial milling, several parameters related to functional properties of the proteins and starch were analyzed. The parameters defining the proteins functionality are wet gluten, Gluten index, deformation energy of dough and minimum torque C2 and allowed establishing significant correlations between wheat and flour. Concerning the starch baking performance, the parameters that allowed establishing significant correlations between wheat and flour are falling number value, amylase activity, starch gelatinization and cooking stability range. Analyzing the trend of variation of the quality parameters given by Mixolab and Alveograph tests for wheat and flour, one can see that it is possible to predict the flour quality based on wheat quality.